Influence of Concussion Education Exposure on Concussion-Related Educational Targets and Self-Reported Concussion Disclosure among First-Year Service Academy Cadets. Issue 3 (2nd December 2019) - Register-Mihalik, Johna K; Kay, Melissa C; Kerr, Zachary Y; Peck, Karen Y; Houston, Megan N; Gildner, Paula; Svoboda, Steven J; Marshall, Stephen W; Cameron, Kenneth L
Abstract: Introduction: Concussion disclosure is often essential for military personnel to receive appropriate care following concussive injury. Concussion-related education and training may play a role in improving disclosure and recognition among peers, allowing for more timely concussion identification and treatment. The objectives of this study were to: (1) describe concussion education exposure among first-year service academy cadets and (2) examine the association between exposure to concussion education sources (multiple vs. only one) and concussion-related knowledge, attitudes, perceived social norms, intention to disclose symptoms, and disclosure behaviors. Materials and Methods: First-year service academy cadets completed a cross-sectional survey to assess perceptions of concussion disclosure during preseason concussion baseline testing sessions. Associations between key cadet characteristics and exposure to multiple concussion education sources were examined using odds ratios and 95% confidence intervals. Linear regression was used to model the continuous measures of concussion-related knowledge, attitudes, and perceived social norms. Log-binomial regression was used to model the categorical outcomes of high perceived control over concussion disclosure (higher vs. lower), intention to disclose (higher vs. lower), and disclosure of all possible concussive events at the time of injury (yes vs. no). The primary predictor for all models was exposure to multiple sources of concussion education (video, coach, medical professional, or other) vs. exposure to only one educational source. All models were adjusted for gender, high school contact sport participation, and previous concussion history. Results: Of the 972 first-year cadets (85% response; age = 18.4 ± 0.9 years; 21.7% female, 29.0% NCAA student-athlete), 695 (71.5%) reported receiving some type of previous concussion education and 229 (23.6%) reported a previous concussion history (206/229 reported the actual number they experienced). Of those reporting previous concussion-related education ( n  = 695), 542 (78.0%) watched a video, 514 (74.0%) talked with a coach about concussion, 433 (62.3%) talked with a medical professional, and 61 (8.8%) reported other sources of education ranging from anatomy teachers to brochures. Overall, 527 (75.8%) reported receiving more than one source of concussion education. Having played a contact sport in high school and having a history of concussion were associated with having multiple concussion education exposures. Being female was associated with lower odds of multiple exposures. Exposure to multiple sources of concussion education was not associated with knowledge, attitudes, perceived norms, or higher intention to disclose concussion symptoms. However, among those with a concussion history, exposure to multiple sources of concussion education was associated with a nearly 40% higher prevalence of disclosing all concussions at the time of injury compared to only one source of educational exposure (67.1% vs. 48.3%; prevalence ratio = 1.4; 95% confidence interval: 0.9, 2.1). Thus, although multiple sources of education may not influence intermediate variables of knowledge, attitudes, perceived norms and intentions, exposure to multiple sources of concussion education may influence actual decision-making around concussion disclosure among first-year service academy cadets. Conclusion: These data suggest disparities in concussion education exposure that can be addressed in first-year cadets. Additionally, findings support the importance and use of multiple sources of concussion education in improving cadet's concussion-related decision-making.